Digital Writing Technologies in Higher Education Theory, Research, and Practice - Kruse, Otto.; Rapp, Christian; Anson, Chris M.; Benetos, Kalliopi; Cotos, Elena; Devitt, Ann.; Shibani, Antonette; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2023)
This open access book serves as a comprehensive guide to digital writing technology, featuring contributions from over 20 renowned researchers from various disciplines around the world. The book is designed to provide a state-of-the-art synthesis of the developments in digital writing in higher education, making it an essential resource for anyone interested in this rapidly evolving field. In the first part of the book, the authors offer an overview of the impact that digitalization has had on writing, covering more than 25 key technological innovations and their implications for writing practices and pedagogical uses. Drawing on these chapters, the second part of the book explores the theoretical underpinnings of digital writing technology such as writing and learning, writing quality, formulation support, writing and thinking, and writing processes. The authors provide insightful analysis on the impact of these developments and offer valuable insights into the future of writing. Overall, this book provides a cohesive and consistent theoretical view of the new realities of digital writing, complementing existing literature on the digitalization of writing. It is an essential resource for scholars, educators, and practitioners interested in the intersection of technology and writing.
Introduction -- Section1: Word processing software -- Name of chapter -- The Beginnings of Word Processing: A Historical Account -- Establishing the Standard: The Rise of Microsoft Word -- Expansions and Alternatives: Beyond Microsoft Word -- Section2: Web applications and platform technology -- Name of chapter -- Hypertext, Hyperlinks, and the World Wide Web -- Creativity Software and Idea Mapping Technology -- Digital tools for Written Argumentation -- Digital Note-taking for Writing -- Synchronous and Asynchronous Collaborative Writing -- Social Annotation: Promising Technologies and Practices in Writing -- Multimodal chat-based apps: enhancing copresence when writing -- Learning Management Systems (LMSs) -- Digital Teacher Feedback Tools -- Digital Student Peer Review Systems -- Reference Management Systems -- Plagiarism Detection and Intertextuality Software -- The Electronic Portfolio: self-regulation and reflective practice -- CMS 3.0: The All-in-One Digital Writing Workspace -- Section3: Writing analytics and language technologies -- Name of chapter -- Automated Text Generation and Summarization -- Information Retrieval and Knowledge Extraction for Academic Writing -- Analytic Techniques for Automated Analysis of Writing -- Automated Scoring of Writing -- Automated Feedback on Writing -- Intelligent Tutoring for Writing -- On Corpora and Writing -- Investigating Writing Processes with Keystroke Logging -- Section4: Implications -- Writing and Learning: What Changed with Digitalization? -- Towards Defining Digital Writing Quality -- Finding the Right Words: Language Technologies to Support Formulation -- Writing and Thinking: What Changes with Digital Technologies? -- Writing processes in the digital age: A networked interpretation -- glossary -- index.
Keywords: Penmanship; Language and languages -- Study and teaching; Educational technology; Literacy; Writing Skills; Language Education; Digital Education and Educational Technology; Literacy